Travels through the states of North America, and the provinces of Upper and Lower Canada, during the years 1795, 1796, and 1797 [Vol. 2 of 2] - Weld, Isaac, 1774-1856 (Salt Lake City, UT : Project Gutenberg, 2021)
"Travels Through the States of North America, and the Provinces of Upper and Lower Canada" by Isaac Weld, Junior, is a historical account written in the late 18th century. This travelogue captures the author's explorations and observations in North America, focusing on the regions of Canada and the United States during his journey from 1795 to 1797. It likely covers a range of themes including geography, social customs, agricultural practices, and encounters with local populations, providing valuable insights into the cultural and economic landscape of the time. The opening of the work describes the author's departure from Quebec and his journey toward Montreal, highlighting the conveniences of travel in this area due to well-established post houses. Weld details the landscape along the St. Lawrence River, noting its beauty and the character of the Canadian horses and drivers. He also provides a brief description of Trois Rivieres, illustrating the town's features and the lifestyle of its inhabitants, particularly in relation to agriculture and social customs. The narrative sets up a travel narrative rich with observations that contrast the lives of Canadians and Americans, indicating the author's intent to compare and analyze the differing cultures and economies of the regions he explores. (This is an automatically generated summary.)
Release date is 2021-08-02
Tim Lindell, Barry Abrahamsen, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: United States -- Description and travel -- Early works to 1800; Canada -- Description and travel -- Early works to 1800